Assessment of Aquifer Vulnerability in Baghmalek Plain in Khuzestan, Iran using GIS DRASTIC Model - Gelareh, Reihany; Kashkuli, Heydar Ali; Zohrabi, Narges (2018)
The purpose of this study was to assess the vulnerability of groundwater in Baghmalek aquifer to pollution. The groundwater vulnerability was simulated in Geographical Information System (GIS) using DRASTIC model. Indeed, GIS clarifies the results of a complicated model through visual representation, which provided an applicable tool for decision makers. The vulnerability map of Baghmalek basin shows four classes including no risk to pollution, very low vulnerability, low vulnerability, and low to moderate vulnerability depending on the intrinsic characteristics. The results of the model indicate that the northern parts of the plain are more vulnerable than the southern parts.
Keywords: Groundwater; Vulnerability assessment; Geographic Information Systems; Water pollution